Final answer:
To solve the equation 3(2x + 6) - 4x = 2(5x - 2) + 6, the first step is to use the distributive property on both sides.
Step-by-step explanation:
To solve the equation 3(2x + 6) - 4x = 2(5x - 2) + 6, we can follow the following steps:
- Use the distributive property on both sides of the equation. This means multiplying the coefficients by each term within the parenthesis. This will result in: 6x + 18 - 4x = 10x - 4 + 6.
- Combine like terms on each side of the equation. On the left side, combining the x terms gives us 6x - 4x = 2x. On the right side, combining the constant terms gives us -4 + 6 = 2.
- Now, we have the equation 2x + 18 = 10x + 2. We can isolate the x term by subtracting 2x from both sides of the equation: 18 = 8x + 2.
- Finally, subtract 2 from both sides of the equation to get rid of the constant term on the right side: 16 = 8x.
Therefore, the first step in solving the equation is to use the distributive property on both sides.